(untitled) (Journal Of Educational and Psychological Researches, 2023)
Sustainable development (SD) is an improvement that meets present needs but jeopardizes the ability of new populations to do the same. It is vital to acquaint EFL students with the terminology and idiomatic expressions of this discipline. Nowadays, sustainable development and the environment have been prioritized in every aspect of life. Since culture and the teaching of Foreign language English cannot be separated, the English language becomes the mean of communication in health, economics, education, and politics. Thus, integrating sustainable development goals within language learning and teaching is very important. This descriptive quantitative study aims to investigate the perception of EFL pre-service teachers of sustainable development. Students in their fourth year at the "College of Education for Women" for the academic year 2021-2022 are selected as the study sample and Balakrishna et al (2020) questionnaire is adopted and modified to be used as the study tool. The validity and reliability of the study tool have been ascertained by using face validity and the Alpha Cronbach formula respectively. Descriptive statistics (frequencies, weighting means, percentages) are used to find the results. The results indicate that EFL student-teachers’ perception of sustainable development is moderate in their perception of sustainable development. Accordingly, suitable recommendations and suggestions are set forward.